2021
DOI: 10.48550/arxiv.2107.04493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ferro-octupolar order and low-energy excitations in d$^2$ double perovskites of Osmium

Leonid V. Pourovskii,
Dario Fiore Mosca,
Cesare Franchini

Abstract: Conflicting interpretations of experimental data preclude the understanding of the quantum magnetic state of spin-orbit coupled d 2 double perovskites. Whether the ground state is a Janh-Tellerdistorted order of quadrupoles or the hitherto elusive octupolar order remains debated. We resolve this uncertainty through direct calculations of all-rank inter-site exchange interactions and inelastic neutron scattering (INS) cross-section for the d 2 double perovskite series Ba2M OsO6 (M = Ca, Mg, Zn). Using advanced … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Despite the seeming success of our phenomenological proposal, our previous work did not identify the microscopic origin of the octupolar order. A very recent study combining ab initio and dynamical mean field theory calculations [37] has found unequivocal evidence of FO exchange -however, the essential ingredients favoring octupolar order were not fully clarified in this work. At the same time, several competing theories have emerged for the phase transition observed in these osmates.…”
Section: Introductionmentioning
confidence: 64%
“…Despite the seeming success of our phenomenological proposal, our previous work did not identify the microscopic origin of the octupolar order. A very recent study combining ab initio and dynamical mean field theory calculations [37] has found unequivocal evidence of FO exchange -however, the essential ingredients favoring octupolar order were not fully clarified in this work. At the same time, several competing theories have emerged for the phase transition observed in these osmates.…”
Section: Introductionmentioning
confidence: 64%